Comparison of Skeletal and Dentoalveolar Effects of Chincup and Chincup + Bite Plate Therapies - Ayça Arman; T. Ufuk Toygar; Eyas Abu Hıjleh (Galenos Yayinevi, 2005)
The aim of this study was to evaluate and compare the skeletal and dentoalveolar effects of chincup and chincup plus bite plate therapies applied to growing Class III patients. The material consisted of lateral cephalometric and hand-wrist films of 37 skeletal Class III cases obtained before treatment and after achieving a Class I relation. 23 cases were treated with only chincup, 14 with chincup + posterior bite plate appliances. The mean pretreatment ages were approximately 11 years and the observation period was 1 year. The cephalometric films were analyzed according to the structural superimposition method of Björk. All tracings were double-digitized and the measurements were calculated by a computer program (PORDIOS). Treatment changes within the groups and the differences between the groups were analyzed statistically. Facial heights increased in both groups, while increase in the upper anterior facial height was more significant in chincup + bite-plate group. Forward positioning of the maxilla was significant in both groups, whereas posterior rotation of the maxilla was significant in chincup + bite-plate group. The mandible was positioned backward, gonial angle decreased significantly in both groups. Posterior rotation of the mandible was more significant in the chincup + bite-plate group. Intermaxillary relationship improved significantly in both groups. The overjet increased and the overbite decreased, upper incisors protruded significantly in both groups. Protrusion of the maxillary incisors were more significant in the chincup + bite-plate group. Mandibular incisors showed retrusion in the chincup, protrusion in the chincup + bite-plate group. Long-term studies are required in order to confirm the success and stability of these changes.